The exercise-regulated myokine chitinase-3-like protein 1 stimulates human myocyte proliferation - Görgens, S W; Hjorth, M; Eckardt, K; Wichert, S; Norheim, F; Holen, T; Lee, S; Langleite, T; Birkeland, K I; Stadheim, H K; Kolnes, K J; Tangen, D S; et al. (Acta physiologica (Oxford, England), 2016)
AIM: Chitinase-3-like protein 1 (CHI3L1) is involved in tissue remodelling and inflammatory processes. Plasma levels are elevated in patients with insulin resistance and T2DM. We recently showed that CHI3L1 and its receptor protease-activated receptor 2 (PAR-2) are expressed in skeletal muscle. Activation of PAR-2 by CHI3L1 protects against TNF-α-induced inflammation and insulin resistance. However, the effect of exercise on CHI3L1 and PAR-2 signalling remains unknown. The aim of this work was to study the impact of exercise on CHI3L1 production and the effect of CHI3L1/PAR-2 signalling on skeletal muscle growth and repair. METHODS: Three human exercise studies were used to measure CHI3L1 plasma levels (n = 32). In addition, muscle and adipose tissue CHI3L1 mRNA expression was measured in response to acute and long-term exercise (n = 24). Primary human skeletal muscle cells were differentiated in vitro, and electrical pulse stimulation was applied. In addition, myoblasts were incubated with CHI3L1 protein and activation of MAP kinase signalling as well as proliferation was measured. RESULTS: Circulating CHI3L1 levels and muscle CHI3L1 mRNA were increased after acute exercise. In addition, CHI3L1 mRNA expression as well as CHI3L1 secretion was enhanced in electrically stimulated cultured myotubes. Incubation of cultured human myoblasts with CHI3L1 protein leads to a strong activation of p44/42, p38 MAPK and Akt as well as enhanced myoblast proliferation. CONCLUSION: Our findings suggest that CHI3L1 is induced by acute exercise and that CHI3L1/PAR-2 signalling activates myocyte proliferation, which is important for restructuring of skeletal muscle in the response to exercise training.
Keywords: dospělí; kosterní svaly; exercise; proliferace buněk; svalové buňky; skeletal muscle; Adult; mladý dospělý; Chitinase-3-Like Protein 1; chitinase-3-like protein 1; lidé; cvičení; signální transdukce; messenger RNA; Muscle, Skeletal; Signal Transduction; RNA, Messenger; Male; Aged; Young Adult; Cell Proliferation; protein CHI3L1; lidé středního věku; senioři; mužské pohlaví; Muscle Cells; Exercise; Middle Aged; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction; Humans